The Influence of Democratic Parenting and Self-Regulated Learning on Students Academic Procrastination in Ngaglik - Mujidin, Mujidin; Rustam, Husnul Khotimah; Salsabella, Difa Sefira (Universitas Syiah Kuala, 2023)
Procrastination can cause significant problems and disrupt the education systems of high school students, including those at State Senior High School 1 Ngaglik. This study examines the influence of democratic parenting and self-regulated learning on students academic procrastination. We performed this quantitative study using a cluster-random sampling technique. Three measurement tools were used: academic procrastination scale, democratic parenting scale, and self-regulated learning scale. In total, 86 participants completed the survey. Data analysis used analyze multiple regression on SPSS. The findings support our initial hypothesis that democratic parenting and self-regulated learning significantly influence academic procrastination. However, the coefficient value of democratic parenting styles influence on academic procrastination was greater than 0.01 (0.245), indicating that the first minor hypothesis is unsupported. The subsequent minor hypothesis testing shows a coefficient value of -0.366 0.01, indicating that self-regulated learning has a significant positive influence on academic procrastination. This finding becomes the basis for explaining how self-regulated learning could contribute to lowering students academic procrastination. Increasing self-regulated learning behavior could motivate students to improve their cognitive and problem-solving skills. We believe that the findings from this research still require more exploration from future studies.